PENGARUH LINGKUNGAN KELUARGA TERHADAP PENINGKATAN PSIKOLOGIS ANAK USIA DINI PERSPEKTIF AL-QUR’AN - Nuraini Subhan; Besse Mutmainnah; Indo Santalia (STKIP Subang, 2025)
This study examines the psychological development of early childhood. The homeenvironment is the first environment for early childhood, besides being part of thefamily environment. In this golden phase, it greatly determines the physical,cognitive, social emotional, and spiritual growth of children. The author usesliterature reviews from several journals that discuss the importance of the role ofthe family in early childhood. A stable and loving family greatly supports thepsychological development of children. On the other hand, an inharmoniousenvironment is at risk of causing emotional disorders and problems in the growthof early childhood. Based on the facts revealed, a positive parenting pattern isneeded, and the household environment is the main key to forming a childscharacter.